Antisipasi Kebisingan Aktifitas Pesawat terhadap Lingkungan Kegiatan di Sekitar Bandara Sultan Thaha Jambi - Handayani, Sari; Das, Amsori M.; Dony, Wari (Jurnal Talenta Sipil, 2025)
As the residents of Jambi Province's demand for air transportation increases, this will certainly have an impact on aviation activities in Jambi, where the intensity of flights continues to increase and the number of passengers increases. Based on these things, this research is intended to identify the extent of the influence of the noise level in the Sultan Thaha Airport area on the activity environment around the airport so that necessary steps can be taken so that residents and school students around the airport can anticipate the impact of noise from aircraft in the area. Jambi Sultan Thaha Airport. The data required in this research is divided into 2 types, namely primary data and secondary data. For primary data in this research, questionnaires were distributed to environmental activity areas around the airport, and for secondary data from this research, data on the population of RT 03. Data collection for measuring noise values was carried out at several points, where these points were the environment. activities in the Jambi Sultan Thaha Airport area. Measurements refer to KEPMENLH No. 48/MenLH/11/1996. The results of the questionnaire data distributed to residents and students in the area around the school which is the activity area of Sultan Thaha Jambi Airport, concluded that people in the activity area sometimes have trouble sleeping, get dizzy, feel uncomfortable and get emotional more easily, due to the distance. close to the runway, which is the main factor in the impact of noise in the area around the school, especially when planes land. An alternative anticipatory method that residents can implement now is to use a natural noise barrier, namely planting trees that meet the criteria so that they can reduce noise exposure.